A Panel of 3 Markers Including p16, ProExC, or HPV ISH is Optimal for Distinguishing Between Primary Endometrial and Endocervical Adenocarcinomas - Kong, Christina S. (Am J Surg Pathol, 2010)
Endometrial and endocervical adenocarcinomas may seem histologically identical and it can be difficult to determine primary site of origin based on morphology alone. As the distinction is significant and cannot always be made on the basis of clinical findings, various immunohistochemical panels have been proposed to aid in determining site of origin. Stains for vimentin, estrogen receptor (ER), progesterone receptor (PR), monoclonal carcinoembryonic antigen, p16 and ProExC, and HPV in situ hybridization (ISH), were performed on 283 tissue microarray (TMA) cores and 38 whole sections. The TMA consisted of 214 endometrial carcinomas, 33 endocervical adenocarcinomas, and 36 problematic cases. The endometrial and endocervical carcinomas represented usual endometrioid and mucinous types, and special variants (uterine serous carcinoma, uterine clear cell carcinoma, minimal deviation endocervical adenocarcinoma, cervical small cell carcinoma, adenoid basal cell carcinoma, mesonephric carcinoma). Univariate analysis showed that 6 markers (vimentin, ER, PR, p16, ProExC, and HPV ISH) performed well in distinguishing between endocervical and endometrial origin for the usual endometrioid and mucinous types. Multivariate analysis showed that vimentin, p16, and HPV ISH are the strongest predictors of site. Using a script written in R, the diagnostic accuracy of all possible combinations of markers was evaluated and it was shown that a 3 marker panel including vimentin, ER, or PR, and an HPV marker (p16, ProExC, or HPV ISH) is optimal for determining site of origin for usual endometrial and endocervical adenocarcinomas. However, these panels do not perform well with special variant carcinomas.